Understanding root causes of homelessness in Marin County, CA and prevention strategies through semi-structured interviews and constant comparative analysis - Michaela F. George; Kelsey M. Bas; Joseph A. Blakely; Naila I. Saghir; Garrett T. Siebels; Liliana Valle-Contreras; Sehrish Khan (Discover Mental Health)
Abstract Introduction Even with the increased prevalence of homelessness in the US, there is limited research that investigates circumstances that can lead to homelessness, especially in affluent communities in California. This lack of understanding, even when resources are available, perpetuates the inequities in health and wellbeing statewide, connection to basic necessities, effective prevention strategies, and meaningful policy changes. Methods This qualitative analysis consisted of a total of 24, semi-structured interviews conducted in the Spring of 2023 by public health researchers. Participants (18 and older) who were seeking support from a local community partner (the Ritter Center) were interviewed. Interviews consisted of a verbal consent in English and a set of IRB approved questions about the participants life circumstances and background that may have led to homelessness. Transcribed interviews were coded, and several themes emerged. Results Thematic analysis supports three main themes: lack of resources, mental health struggles and past trauma, and safety and health issues. Lack of resources draws attention for more access to sustainable housing opportunities to prevent homeless in the first place. Struggles with mental health stemmed from extreme childhood trauma including stories of abandonment. Substance use and misuse were reported both before and after experiencing homelessness. Many participants expressed current concerns about their relationship with safety and overall health for many years. Conclusions Common themes suggest that there are recurrent circumstances that lead to individuals experiencing homelessness. Understanding the root causes of homelessness can help public health departments, local government and organizations implement upstream interventions to prevent the perpetuation of homelessness.